Graffitis and Stencils: The Construction of Space in the City (Palimpsesto, 2019)
The major premise of this article is the construction of spaces from graffiti and stencil, emphasizing the appropriations and changes after a morphological and social intervention. The articulation of the graphics transforms the space, giving it a new meaning and functioning, in it, codes, symbols and signs are linked to create social, cultural and political dynamics, which are inserted in the imaginary of the city inhabitants and introduce new elements in the space spectrum.
Keywords: Graffiti; Stencil; City; Space; Social; Imaginary spaces